Blue Nevus and Malignant Blue Nevus. Issue 2 (March 2015) - Sugianto, Jessica Zarah; Ralston, Jonathan Scott; Metcalf, John S.; McFaddin, Courtney L.; Smith, Tim
Abstract : Abstract: Blue nevi are a heterogeneous group of lesions that can display a variety of different clinicopathologic characteristics. Although attempts are made to classify each lesion into defined subtypes, there can be overlap between the subtypes. The clinical and histolopathologic features of common blue nevi and cellular blue nevi are discussed, as well as blue nevi with atypical features and malignant lesions with features of blue nevi.